A Metric-Based, Meta-Analytic Appraisal of Environmental Enrichment Efficacy in Captive Primates - Duncan, Luke Mangaliso; Pillay, Neville (Animals (Basel), 2025)
Non-human primates (hereafter ‘primates’) constitute a common group of animals in captivity but their captive maintenance involves ethical and husbandry issues, many of which can be addressed through environmental enrichment (hereafter ‘enrichment’). Enrichment is often applied in a trial-and-error fashion or based on subjective assessments of efficacy. Thus, a predictive framework for enrichment is necessary to ensure it achieves the desired outcomes. As one of the initial steps towards the development of a predictive enrichment science, we aimed to identify the most effective enrichment approaches for captive primates. We conducted a comprehensive meta-analysis of the peer-reviewed literature and extracted information on methodological approaches, experimental design, species and environmental context. We developed and applied a novel efficacy index score to each study protocol as a comparable metric of enrichment efficacy in order to appraise current enrichment practices. Our findings suggest that captive primate enrichment approaches vary in their efficacy, with training-based enrichment being the most effective. Furthermore, the social context of subjects appears to influence efficacy, with primates housed alone deriving the most benefit from enrichment. A species’ natural minimum group size may also influence enrichment efficacy but this relationship requires further investigation. Testing and reporting trends for captive primate enrichment are presented and discussed, highlighting important gaps in the literature and avenues of future research while identifying the beneficial effects of different enrichment practices.